Wasathiyah Librarianship sebagai Model Pengelola Informasi dalam Menghindari Bibliosida: suatu pendekatan konseptual - Hidaya, Almer Samantha (Pustabiblia: Journal of Library and Information Science, 2025)
This study explores the concept of wasathiyah librarianship as an Islamic moderation-based model of information management aimed at preventing bibliocide. Employing a descriptive qualitative method through library research, the study draws on primary and secondary sources related to wasathiyah values, librarianship, and bibliocide. The data were analyzed thematically using an interpretive qualitative approach. Findings reveal that implementing the seven pillars of wasathiyah—tawassuth (moderation), i’tidal (justice), tasamuh (tolerance), syura (consultation), islah (reconciliation), qudwah (exemplary behavior), and muwathanah (nationalism)—can foster an inclusive, just, and dialogical librarian paradigm. Librarians who embody these values are positioned to resist censorship, marginalization of information, and monopolization of narratives, thereby supporting a pluralistic and peaceful information ecosystem. The study concludes that wasathiyah librarianship is not only ethically relevant for professional practice but also serves as a strategic approach to safeguarding collective memory against bibliocide. This model should be further developed in Indonesian library policies, especially within religious high educational institutions.